Effect Of Diffrent Amount Of Salts On Detoxification And Some Chemical Properties Of Municipal Solid Waste Leachate - MEHRNOUSH ESKANDARI TORBAGHAN; ALIREZA ASTARAEI; MASOUD ESKANDARI TORBAGHAN (International Journal of Pharma and Bio Sciences, 2011)
Water is the main part of municipal sewage comprising 99 to 99.5 percent of sewage. Since, MS water and MSW leachate are having high EC and toxicity effects; water treatment with chemicals is used to decrease microbial contamination and toxicity. Coagulants such as ferric chloride, alum, etc. are usually used in coagulation as a common process in water treatments. A laboratory experiment was performed to study the effects of three different coagulants of copper sulfate, ferric chloride and sodium benzoate in two levels of 40 and 80 mg l-1 on microbial detoxification and on chemical properties of municipal solid waste leachate. Electrical conductivity and total soluble organic carbon decreased in all treatments if compared to control (pure leachate).Solutions of 40 mg l-1 ferric chloride, 40 and 80 mg l-1 sodium benzoate were more efficient in reducing total number of microorganisms. Copper sulfate at 40 mg l-1 had greater effect in reducing number of fecal and non fecal coli forms whereas, sodium benzoate had maximum reduction in number of fungi at 40 mg l-1.